International interaction in the context of political processes of post-Soviet Russia: structural and institutional analysis - V. A. Matvienko (Проблемы постсоветского пространства)
The article reviews the main problems of international interaction in the political space of post-Soviet Russia. This research topic has been a burning and vital issue of the day over the last years. Moreover, it has become even more significant and urgent nowadays. From time to time the number of racial tensions and inter-ethnic conflicts is increasing everywhere. This fact is likely to indicate some disadvantages and faults of evaluating the state of international interaction. One of the reasons why it happened is the fact that scholars have not come to an agreement about this issue yet. Having thoroughly examined the current scientific theories and research areas, the author of the article took into consideration the most popular and widespread points of view on the problem. Such factors as the soviet «heritage», integration of ethnic minorities into the cultural space of civil nation, a great many opportunities for preserving national identity, etc. influenced the principles of international interaction in the political space of modern-day Russia. The results of the analysis of the above mentioned factors can be put into practice with a view to assess the potential of international interaction which will let predict their social and political importance and reveal possible flash seats of conflictogenity. The author’s attention is focused on considering the issues of the role of the government in the optimization of inter-ethnic relations. The main fields of concern of public authorities have been investigated. Policy papers and special-purpose programmes have been scrutinized. The author has also outlined the leading political figures’ attitude to this acute problem.